Advancing spotted babylon broodstock performance and sustainable aquaculture practices through natural and formulated feeds - Saweit Chaimongkol,; Supat Khongpuang,; Chinnawat Pitagsalee,; Amrin Thongwaan,; Hangsapreurke, Krasindh (Maejo International Journal of Energy and Environmental Communication, 2023)
In the approach to optimize spotted babylon (Babylonia areolata) broodstock nutrition within hatchery environments, two distinct experiments were conducted. The first focused on broodstock, having an average weight of 43g. They were exposed to various natural feeds, with yellow stripe trevally being a notable inclusion, and they were kept at a density of 50 snails/m2. The following phase centered on juveniles, assessing the impact of replacing fishmeal with beef scraps and bonemeal in different proportions: 0%, 10%, 20%, and 30%. Yellow Stripe Trevally meat was used as a comparative control diet. These juveniles were kept at a density of 180 snails/m2. Both experimental groups were housed in standardized tanks, benefiting from a consistent 12-hour seawater supply daily. Through diligent monitoring, we observed that the trevally diet led to marked improvements in the growth and reproductive performance of the broodstock. On the other hand, for the juvenile group, the traditional diet was superior up to the 20% fishmeal substitution level. However, the growth rate diminished notably with a 30% substitution. Across the board, there was a consistent survival rate among all experimental groups. In sum, this study’s findings underscore the effectiveness of yellow stripe trevally as a potent feed for broodstock. Additionally, when considering juvenile diets, fishmeal substitution with beef and bonemeal should be approached cautiously, ideally at most 20%.